Acquainting English to Young Learners through Nursery Rhymes at Playgroup (PIAUD IAIN Kudus, 2022)
Most children like and enjoy singing songs. It can be used as one of materials for foreign language learning. Using nursery rhymes in the classroom can be a great break from following a set curriculum. This study aims to know the way to acquaint English to young learners through nursery rhymes, to identify the criteria of nursery rhymes that suits on the students, and to know the strengths and challenges in acquainting English to young learners through nursery rhymes at Playgroup. Qualitative research was employed to conduct this study. To collect the data, some techniques were carried out namely observation, interview, and documentation. The results revealed that the acquaintance of young learners English through nursery rhymes considers the content; students’ readiness, and class atmosphere, the nursery rhymes must teach the character education; the strengths in acquainting English to young learners through nursery rhymes at Halimatus Sa’diyah playgroup are the commitment among the manager/organizers, teachers and parents and the high awareness that English is important. And, the challenges are low teacher’s pedagogical competency, facilities, curriculum/material, and non-English school or living environment.